Comparative Study of PT. Tower Bersama’s Performance Pre-Post PSAK 73 Implementation - Clara, Rahma; Ristiyana, Rida; Sani, Abdillah (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The implementation of PSAK 73 brings significant changes in financial reporting, especially regarding lease obligations in a company. This research aims to see whether there are differences in company performance and taxation before and after the implementation of PSAK 73 on rent. This type of research is descriptive comparative with research data using annual financial reports with research data using financial reports from 2017-2022 at PT. Tower Bersama Infrastructure, Tbk. The data analysis technique in this research uses SPSS version 25 with the Normality Test (Shapiwo-Wilk) and the Difference Test (Paired Sample Test). The results of this research show that there are differences before and after the implementation of PSAK 73 in company performance as proxied by the Debt to Asset Ratio, whereas there are no differences before and after the implementation of PSAK 73 in company performance as proxied by the current ratio, return on assets, return on equity, debt to equity ratio, and taxation (final tax) before and after implementing PSAK 73.